Between Text and Practice: The Reception of Ja'far bin Abi Thalib's Hadith in the Nyusur Tanah Tradition - Ismatulloh, A.M.; Ismail, Ismail; Zain, Muhammad Fuad (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
This study examines the nyusur tanah tradition in Dayeuhluhur Village, Cilacap, as a concrete manifestation of living hadith, where Islamic teachings are continuously reinterpreted through local cultural practices. Although post-death rituals are widely practiced among Muslim communities, there has been limited scholarly focus on how specific hadiths, such as the narration concerning Jaʿfar bin Abi Thalib, are integrated into communal traditions. This research employs a qualitative, phenomenological method grounded in postpositivist philosophy, involving fieldwork through in-depth interviews and participant observation with religious leaders (kiai) and residents. The study reveals a unique practice in which neighbors, not the bereaved family, prepare food for mourners, an inversion of dominant funeral customs. This practice is rooted in the Prophet's instruction to support grieving families, reflecting how hadith operates as a dynamic moral guide rather than solely a textual source. The Kiai are vital as cultural brokers, aligning tradition with Islamic values. This study contributes to the discourse on living hadith by demonstrating its role in sustaining cultural identity while maintaining religious authenticity within a plural cultural landscape.